Determining ESG Performance: The Role of Audit Committees, Women on Boards, and Eco-Innovation - Andreani Hanjani; Puspita Dewi Wulaningrum; Prasetyono; Beta Pujangga Mukti (Jurnal Riset Akuntansi dan Auditing, 2026)
This study aims to examine the influence of audit committees, women on boards, and eco-innovation on ESG performance. The sample consists of 442 companies listed on the Indonesia Stock Exchange in 2019-2024, purposive sampling selected. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) with smartPLS. The results show that ESG performance is positively and significantly influenced by audit committees, women on boards, and eco-innovation. This study offers novelty by integrating corporate governance mechanisms and eco-innovation within a single analytical framework to explain the determinants of ESG performance in emerging markets such as Indonesia. This study provides theoretical contributions by strengthening the relevance of agency, stakeholder, and legitimacy theories in explaining governance mechanisms and eco-innovation participation in increasing transparency, accountability, and corporate desire. Practically, it serves as a reference for regulators and policymakers in Indonesia in formulating policies related to strengthening corporate governance, increasing women's representation in board direction, and encouraging eco-innovation practices to improve corporate ESG performance. This study has not considered the possibility of a two-way causal relationship (endogeneity), where companies with good ESG performance are potentially more attractive to have stronger governance structures, including effective audit committees and women on the board of directors. Abstrak - Studi ini bertujuan untuk meneliti pengaruh komite audit, women on boards, dan eco-innovation terhadap kinerja ESG. Sampel terdiri dari 442 perusahaan yang terdaftar di Bursa Efek Indonesia pada tahun 2019-2024 yang dipilih berdasarkan purposive sampling. Data dianalisis menggunakan partial least squares structural equation modeling (PLS-SEM) dengan smartPLS. Hasil penelitian menunjukkan bahwa kinerja ESG dipengaruhi secara positif dan signifikan oleh komite audit, women on board, dan eco-innovation. Studi ini menawarkan kebaruan dengan mengintegrasikan mekanisme tata kelola perusahaan dan inovasi lingkungan dalam satu kerangka analitis untuk menjelaskan penentu kinerja ESG di pasar negara berkembang seperti Indonesia. Studi ini memberikan kontribusi teoritis yaitu memperkuat relevansi teori agensi, pemangku kepentingan, dan legitimasi dalam menjelaskan mekanisme tata kelola dan inovasi lingkungan berpartisipasi dalam meningkatkan transparansi, akuntabilitas, dan keinginan perusahaan. Secara praktis, sebagai referensi bagi regulator dan pembuat kebijakan di Indonesia dalam merumuskan kebijakan terkait penguatan tata kelola perusahaan, peningkatan representasi perempuan dalam arahan dewan, dan mendorong praktik inovasi ramah lingkungan untuk meningkatkan kinerja ESG perusahaan. Penelitian ini belum mempertimbangkan kemungkinan hubungan sebab-akibat dua arah (endogenitas), di mana perusahaan dengan kinerja ESG yang baik berpotensi lebih menarik untuk memiliki struktur tata kelola yang lebih kuat, termasuk komite audit yang efektif dan perempuan di dewan direksi.